Bioethanol production by baker's yeast in opts - effect of temperature and ph - Farah Fadhilah, Fahrur Razi (2014)
This paper presented bioethanol production in oil palm trunk sap (OPTS) by using baker's yeast - effect of temperature and pH. Baker's yeast as known as Saccharomyces cerevisiae. Due to rapid growth in population and industrialization, ecofriendly bioethanol demand is rising rapidly wbrldwide. Bioethanol offers more advantages than fossil fuel since it provides renewable and sustainable sources of energy. The most commonly. employed methods for bioethanol generation are fermentation using baker's yeast (Ahrnad et al., 2011). Baker's yeast is commonly used because it is the cheapest strain available for conversion of V V biomass substrate and produces high yield of ethanol. Due to the cost of raw materials, the cheap renewable agricultural wastes are chosen as alternative substrates to produce ethanol. This study is focused on studying the parameters of temperature, (27 t-39 °C) and pH (3-7) for bioethanol production from oil palm trunk sap (OPTS) by baker's yeast, Saccharomyces cerevisiae. The yeast is grown in nutrient broth (NB) and ferment in oil palm trunk sap (OPTS) medium at- different conditions. By analyzing temperature and pH parameters, specific growth rate, glucose consumption rate, specific ethanol production- and production yield of ethanol can be determined. The analytical technique involved is high-performance liquid chromatography (HPLC) for glucose consumption and ethanol production while cell dry weight (CDW) is determined for growth. From this study, the maximum pH and temperature for bioethanol production were determined to be pH. 6 and 30 °C respectively. The maximum concentration of bioethanol for pH was 34.4 g/L while maximum concentration of bioethanol for temperature, it was 43.4 g/L. In addition, the maximum bioethanol production yield was 0.6 g/g at pH 6 and the maximum bioethanol production yield at temperature at 33 °C was 0.46 g/g. The maximum production yield was contrast with to maximum bioethanol production. This is because the total sugar concentration at 30 °C was too high compared to others: This level might exceed sugar critical level and cause substrate, inhibition to occur. This factor inhibited the ethanol productivity to be produced in high level. Last but not least, it could be concluded that the optimum pH and temperature for growth and production of bioethanol using S. cerevisiae in OPTS were in the range of pH 5-6 and temperature 30 -36°C.